Numerical Simulation on the Radar Cross Section of Variable-Sweep Wing Aircraft - Chen,Shichun (2015)
ABSTRACT: The influence of variable-sweep wing on the aircraft's radar cross section (RCS) characteristics has been studied to reduce the aircraft's RCS as well as its detection probability by the hostile radar. With the help of CATIA, a 3-D digital model of the variable-sweep wing aircraft is built to generate a series of digital grids. Using MATLAB, a numerical simulation on the RCS of variable-sweep wing aircraft is conducted based on physical optics (PO) method and equivalent currents method (ECM). The results of mathematical statistics and comparative analysis show that: (i) the RCS peak value in the head direction of the aircraft decreases non-linearly with the sweep angle of the wing's leading edge; (ii) the azimuth angle corresponding to one of the peak values of the aircraft's RCS is equal to the leading edge's sweep angle; (iii) when the leading edge's sweep angle is 33º, the arithmetic average value of the RCS values in the head direction of the aircraft is 0.644% of the average value when the sweep angle is 0º; (iv) the larger the sweep angle is, the lower the probability that the aircraft is detected.